2004
DOI: 10.1094/cchem.2004.81.1.134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Baking Method and Fermentation on Folate Content of Rye and Wheat Breads

Abstract: Cereal Chem. 81(1):134-139The effect of baking method on folates of rye and wheat breads, as well as the effect of sourdough fermentation of rye, were examined. Sourdough fermentations were performed both with and without added yeast, and samples were taken throughout the baking process. Samples were analyzed microbiologically for their total folate content after trienzyme extraction. Individual folate vitamers were determined by HPLC after affinity chromatographic purification. The lowest folate contents for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
120
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(129 citation statements)
references
References 23 publications
7
120
0
2
Order By: Relevance
“…The increase in the all native folate forms from flour to proofed dough stage were observed. This results are in good agreement with the findings of earlier investigators, who found significantly increase of total folate during sourdough fermentation both wheat and rye flours [19,20]. They reported of some changes in native folates distribution during proofing.…”
Section: Added Folic Acid and Endogenous Folates In Wheat Breadssupporting
confidence: 93%
See 1 more Smart Citation
“…The increase in the all native folate forms from flour to proofed dough stage were observed. This results are in good agreement with the findings of earlier investigators, who found significantly increase of total folate during sourdough fermentation both wheat and rye flours [19,20]. They reported of some changes in native folates distribution during proofing.…”
Section: Added Folic Acid and Endogenous Folates In Wheat Breadssupporting
confidence: 93%
“…It is believed that folate enrichment in certain bioprocessed food could be achieved by using strains of baker's yeast better at producing folate compared to traditional species. Although 5-formyltetrahydrofolate is believed to be the most stable form of reduced folate [20][21][22], the highest decrease of this derivative during baking was noted. In our study as well as that of Osseyi et al [19] baking process did not reduced the level of 5-methyltetrahydrofolate but even 51% increase from flour to bread stage was observed.…”
Section: Added Folic Acid and Endogenous Folates In Wheat Breadsmentioning
confidence: 99%
“…Previous studies have also reported a loss of 7% to 67% endogenous 5-CH 3 THF when proofed dough is baked at about 240˚C for 40 min [10,12]. Biodar has referred to their unpublished data that reported the micro-encapsulated 5-CH 3 THF-Ca (using inert carriers) is about 90% recoverable from baked bread, and 75% recoverable from breakfast cereals, in which it had been incorporated during the manufacturing process [25].…”
Section: Fortification Of Biscuits With 5-ch 3 Thfmentioning
confidence: 99%
“…There have been few studies where the effect of bread baking on folate compounds is studied but there is no data on stability of 5-CH 3 THF vitamer in biscuit [10][11][12]. This project is aimed at investigating the delivery of encapsulated and unencapsulated 5-CH 3 THF into the biscuit and the recovery of 5-CH 3 THF under different baking times and temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Folatos são encontrados em produtos de bioprocessos como produtos lácteos 10 e de panificação 33,3,26 , mostrando que as leveduras, mesmo em processos de transformação de alguns tipos de produtos de origem animal e vegetal, mantêm e/ou aumentam a quantidade de folatos originalmente presentes nesses alimentos 26 .…”
Section: Quantificação De 5-metiltetrahidrofolato No Processamento E unclassified